The development of the incidence of non-neoplastic diseases of the digestive system in adults evacuated from the 30-kilometer zone of the Chornobyl nuclear power plant during the post-accident observation period (1992–2016) (Environment & Health, 2022)
Objective: We analyzed the absolute risk of the development of the incidence of non-neoplastic diseases of the digestive system in adults evacuated from the 30-kilometer zone of the Chornobyl NPP over 1992–2016 epidemiological surveillance.Materials and methods: For the epidemiological study of the incidence of non-neoplastic diseases of the digestive system in the evacuated from the 30-kilometer Chornobyl zone after the Chornobyl accident in 1992–2016 we formed a cohort of 7,143 people aged 18 years and older (2,198 men and 4,945 women). To study the features of the incidence of diseases of the digestive system over the years of observation, we calculated the epidemiological indicator - the absolute risk of development (AR).Results: During 1992–2016, 13,532 cases of the diseases of the digestive system: 3,298 (24.37%) – in men; 10,234 (75.63%) - in women) were revealed for the first time. The absolute risk of the development of digestive diseases makes up 467.64 ± 2.93 cases per 103 man-years of observation (further cases/103 man-years). It was found that 91.05% (12,321 cases) with an absolute risk of 425.32 ± 5.89 93 cas./103 man-years ( 423.22 ± 5.89- in men, 426.19 ± 3, 34 - in women) belonged to the class of the diseases of digestive system (C00-C93). Mostly diseases of oral cavity, salivary glands and jaws (C00 – C14) (200.63 ± 4.77 cases/103 man-years), esophageal diseases, stomach and duodenum (C20 – C31) (146.26 ± 4.21 93) were manifested. Significant loss of health was also caused by the diseases of the gallbladder, biliary tract and pancreas (C83–C87) (50.23 ± 2.60 93), liver disease (C70-C77) – (22.44 ± 1.76 93), non-infectious enteritis and colitis (C50–C52) – (3.93 ± 8.75), other intestinal diseases (C55–C63) – (1.83 ± 0.51) respectively. Irrespective of gender, the development of the incidence of non-neoplastic diseases of the digestive system is characterized by the identity of the diseases and the ratio of their values to the total cohort. However, women suffered more from the diseases of the gallbladder, biliary tract and pancreas, diseases of the oral cavity, men – from the diseases of esophagus, stomach and duodenum.Conclusions:1. The revealed features of the development of digestive diseases in the evacuated from the 30-kilometer zone of the Chornobyl NPP (high absolute risks of diseases of oral cavity, salivary glands and jaws (C00–C14), diseases of esophagus, stomach and duodenum (C20–C31), biliary diseases bladder, biliary tract and pancreas (C80–C87)) need the improvement of medico-social measures to provide qualitative treatment-and-preventive, rehabilitative care from the primary level of medical care.2. It is necessary to conduct medico-educational work on radiation hygiene, regimen, food intake and dietary nutrition for the minimization of the development of established prior nosological forms in the evacuees from the 30-kilometer zone of the ChNPP.
Keywords: evacuees; digestive diseases; epidemiological study